A dimensão técnico-operativa no exercício profissional dos Assistentes Sociais nos Centros de Referência Especializados de Assistência Social - CREAS do Polo Regional de Sinop - Silva, Lauriane Borges Sampaio da (2020)
The main objective of this dissertation is to analyze the forms of expression of the technical-operative dimension in the professional practice of Social Workers in the Specialized Reference Centers for Social Assistance - CREAS, of the Sinop-MT Regional Pole, based on the understanding that this dimension it is the one that comes closest to professional practice, and, for this reason, it explains the totality of the theoretical-methodological and ethical-political dimensions that constitute professional practice. The interest in this research comes from his experience as a Social Worker working in the Social Assistance Policy for twelve years, which allowed him to know the complexities that go through everyday life and that challenge to reaffirm the private attributions, professional actions and the Professional Political Ethical Project in this space occupational partner. In order to carry out the analysis and achieve the defined objectives, a qualitative descriptive research was developed, using the semi-structured interview as a primary source of data, carried out with five Social Assistants who work in the CREAS of the Sinop Regional Pole, and as secondary sources public documents and bibliographic references. From the sources used, it was possible to reflect, through analysis, on the difficulty of Social Workers in articulating the technical-operative, theoretical-methodological, and ethical-political dimensions, in a reflective and planned way. We identified that the forms of expression of the technical-operative dimension were reduced to the application of instruments and techniques, and this fact may be related to the instrumental rationality that permeates the current context and that has prompted the professional to take immediate, punctual and fragmented actions, submitting the professional exercise to technicality and the reproduction of conservative and immediate practices. The institutional challenges and limits have an impact both on the understanding of professional attributions and competences, in the sense of differentiating them from institutional determinations and users' demands, as well as on the development of professional exercise and autonomy, and therefore, it is necessary to seek alternatives to enable the construction of a critical-reflective professional exercise through permanent education, in addition to strengthening the category through participation in the meetings of the committees of the CFESS / CRESS group and the SUAS workers forum in Mato Grosso.